Perceptual Learning and Aging: Improved Performance for Low-Contrast Motion Discrimination - Bower, Jeffrey; Watanabe, Takeo; Andersen, George J. (Frontiers in Psychology, 2013)
Previous research has shown age related differences in discriminating motion at different levels of contrast (Betts, Sekuler, & Bennett, 2009; 2012; Betts, Taylor, Sekuler & Bennett, 2005). A surprising result of this research is that older as compared to younger observers showed improved performance in detecting motion of large high contrast stimuli suggesting age-related differences in center-surround antagonism. In the present study we examined whether perceptual learning methods could be used to improve motion discrimination performance for older individuals under high- and low-contrast conditions. The stimuli were centrally presented Gaussian filtered sine-wave gratings (Gabors) that were either 5 or 0.7 degree diameter with contrast of 0.92, 0.22, or 0.028. Older and younger participants received 3 days of training. The task was to identify if the motion direction was leftward or rightward. Duration thresholds for motion discrimination were derived using two randomly interleaved staircases and compared between pre-/post- test sessions. Both older and younger subjects showed lower duration thresholds as a result of training. The improved performance, for older subjects, due to training was observed for all size and contrast conditions, with training with small low-contrast stimuli resulting in a 23% improvement in motion discrimination performance. Older observers, as compared to younger observers, did show evidence of decreased spatial suppression across all contrast levels. These results suggest that perceptual learning techniques are effective for improving motion discrimination performance, especially for conditions that are difficult for older individuals.